2022
DOI: 10.1109/access.2022.3159231
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning-Based Method for Wind Fields Forecasting Utilizing GNSS Radio Occultation Data

Abstract: With the development of computer technology and expanding environmental issues, machine learning has received more and more attention in the field of weather forecasting. Global Navigation Satellite System-Radio Occultation(GNSS-RO) technology is a kind of remote sensing technology. This investigation proposes an alternative to numerical weather forecasting model. The new method is based on machine learning utilizing GNSS-RO data to forecast the wind field in the Beijing-Tianjin-Hebei region of China. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Unlike other algorithms, this method is not influenced by temperature variations, showcasing its remarkable flexibility. Lahouar et al [13] studied hour-ahead wind power forecasting. They observed that neural networks are sensitive to irrelevant data, with model performance decreasing as the number of features increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other algorithms, this method is not influenced by temperature variations, showcasing its remarkable flexibility. Lahouar et al [13] studied hour-ahead wind power forecasting. They observed that neural networks are sensitive to irrelevant data, with model performance decreasing as the number of features increases.…”
Section: Introductionmentioning
confidence: 99%
“…Several scientists endeavour to employ DL models in wind power prediction using past data to enhance the precision of wind power forecasting [20][21][22]. Recently, there has been an extensive exploration into the realm of DL, focusing on its implementation in short-term wind power prediction [13]. LSTM and CNN are recognised as the two primary DL models [23].…”
Section: Introductionmentioning
confidence: 99%